O turismo na periferia do capitalismo: a revelação de um cartão postal - Amaral Junior, José Bento Carlos (2008)
Tourism has expanded considerably over the past few decades, with an annual movement of almost a million tourists, revenues of 4 trillion dollars per year and the provision of more than 280 million people with a job. The gigantic proportions of this activity arouse the interest of the government and businessmen. Furthermore, the combined actions to exploit tourism in various localities have also drawn scholars attention to the impacts of such actions on the affected communities. The common rhetoric of the authorities and private enterprise regarding tourism is known and emphasizes the benefits that sound doubtful to the receiving communities. This is because it almost always exalts the generation of foreign currency for the country and the development of a region in terms of job and wealth creation, omitting the social problems created. In this sense, the present thesis aims at evaluating the social impacts produced by mass tourism in Brazilian autochthonous communities. With a view to this end, two analyses were elaborated. The first one was based on secondary research on the subject in the literature, in respect to the impacts caused by tourism, its characteristics, sources and progress throughout time, leisure and work, besides a critical analysis of the public policies for tourism in Brazil. The second analysis was a product of a primary survey in two sites located on the Northern coast of the state of Bahia, with different stages of tourism exploitation, where the residents of these communities were interviewed. For the qualitative survey, the oral history method was adopted, based on an interview guide, involving 26 people. The quantitative survey was based on a structured questionnaire for 80 participants. The analysis of the specialized bibliography has conducted us to the conclusion that tourism, which was intensified after the second half of the 20th century, has mingled itself with the human history and nowadays is considered a mass activity. Leisure and tourism possess similarities and have consequences on people's lives, as a means of getting away from it all. However, they are not only related to leisure since they involve themselves with other segments of the economic activity and with different fields of study ¾ trips of a business, religious or scientific-cultural nature ¾ in addition to a tight bond with the national accounts, more specifically with the balance of payments. In terms of public policies in Brazil, we conclude that they are disconnected, fragmented and insufficient to promote the development of a locality or region since, apart from concentrating more than 60% of the resources only in the hotel and catering industry and funding multinationals, they are not creating the expected number of jobs and those that really create jobs, are entry-level and badly paid ones. Government resources for investment in tourism have also obtained contributions from international agents, but this type of funding lacks adequate mechanisms of control and inspection by the government, with a connotation of showing favor to a "clientele" in exchange for votes in political elections. Field survey results have shown that promises made by the government and businessmen of the sector in question are not actually accomplished, causing disbelief, conflicts and frustration in the population of the affected communities. The discourses of wealth creation and development made by these tourism promotion agents are far from the current reality, particularly, as regards jobs, education, public health and safety. Narratives gathered by the qualitative survey pointed to a critical situation in relation to social impacts caused by tourism, e.g. the site of Praia do Forte, which is in a more developed stage. In this specific case the economic and social order was changed, the traditional way of life was replaced by a "modern" one, apart from other events that accompanied these changes like social dislocation, price rises, in addition to social problems that didn t exist in the past and that nowadays are part of the daily life of the communities in the vicinity. At the site of Costa do Sauípe, in a more recent development stage, the slackness of the public authorities and businessmen is glaring and causes traumatic consequences to the population of the surrounding communities. However, for both studied sites, to a greater or lesser extent, the main social impacts observed were problems related to people moving out of their residences, the rise in prices for goods and services, uncontrolled invasion of people in the communities, emergence of violence, drugs and prostitution, absolute disbelief in the public authorities and tourism businessmen, fragmentation of the coordination among local leaders, failure of expectations, especially in relation to jobs and the severance of traditional social relationships. However, the surveys, particularly the quantitative one, indicated that people still express their optimism about the future and that something good has remained, as the learning gained with past experiences, the improvement of some equipment of the local infrastructure and the interest in studying in order to get better life conditions. In contrast to the literature, we do not notice the impact on the hosts of the so called demonstration effect , that was minimum. The tourism promotion agents, not the tourists, were indignant at this. Notwithstanding this, we highlight that the current participation model of the Public Power concerning this activity should not continue. The government must be better prepared to deal with tourism under each of the aspects, namely, investments, inspection, regulation, priority measures to promote development and moreover, to listen to the population in order to cater for their real needs, desires and vocations, so that they can take appropriate action. Current government practices allow property speculation to take place, enriching a few and impoverishing many